The relationship between social capital and postpartum depression symptoms of lactating women in minority areas—A cross-sectional study from Guangxi, China - Qin, Yinghua; Guo, Pengfei; Li, Jiacheng; Liu, Jingjing; Jiang, Shengchao; Yang, Feng; Wang, Rizhen; Wang, Jiahui; Liu, Huan; Zhang, Xin; Wang, Kexin; Wu, Qunhong; et al. (Frontiers in Psychology, 2022)
Background Postpartum depression (PPD) is the most common mental illness affecting women during lactation, and good social capital is considered a protective factor. This study aimed to investigate PPD symptoms, and explore the relationships between social capital and PPD symptoms of lactating women in southwest minority areas in China. Materials and methods This cross-sectional study was conducted among 413 lactating women in Guangxi, China. Data were collected using the Edinburgh Postnatal Depression Scale and the Chinese version of the Social Capital Assessment Questionnaire. Hierarchical regression analysis was conducted to explore the factors influencing PPD symptoms, and a structural equation model was used to examine how social participation and cognitive social capital mediated PPD symptoms. Results The total prevalence of PPD symptoms (score > 12) was 16.46%, and that of mild depression symptoms (9–12 score) was 22.03%. Nine variables predicted PPD symptoms and explained 71.6% of the variance in the regression model: higher age, lack of medical security, fixed occupation, breastfeeding time, self-caregiver, maternity leave, social participation, social trust, and social reciprocity. Furthermore, cognitive social capital mediated the relationship between social participation and PPD symptoms, with a mediation effect rate was 44.00%. Conclusion The findings of this study highlight that social capital, support from family members, maternity leave, and medical insurance play protective roles in the PPD symptoms of lactating women. It is necessary to improve social capital as a key strategy for interventions for PPD symptoms, and active social participation activities are critical to reducing PPD symptoms among lactating women in minority areas.